Banking Evaluation System with Indicators (CAMELS) in Light of Risks: An Applied Study on the Iraqi Middle East for Investment for the Years from 2006 to 2009 - محمد سمير دهيرب (Iraqi Journal for Administrative Sciences, 2024)
The research shows the banking evaluation system using indicators (CAMELS) through a case study of the Iraqi Middle East Investment Bank to identify banking risks that constitute weak points in the financial, operational, and administrative operations of the bank. The descriptive and deductive approach was used in collecting and analyzing the published financial data of the Middle East Investment Bank based on the CAMELS system for the four fiscal years from 2006 to 2009, and the most important results of the research indicate that the Middle East Bank obtained the first level (rating 1) according to the composite evaluation policy of the CAMELS system, which means that the bank is fundamentally sound and gives indications that Its performance is strong in terms of profits and the good growth of its assets, and the management’s experience in following up on banking operations, analyzing the risks related to them, and determining appropriate levels of capital needed for them is good, in addition to the reasonableness of the distribution of profits. The study showed the importance of applying the American banking evaluation system, as it highlighted the positive aspects of applying the system and its role in feedback and control with information that reveals some aspects of weakness and shortcomings and their causes. The CAMELS system also works to conduct a comprehensive analysis of the bank’s performance and compare it with the industry level in the banking environment, which contributes to drawing up a solid policy and plans for management by focusing on the negative elements that need special attention. Here it is necessary to point out the most important recommendations, including the necessity of implementing the system. On private banks annually to achieve benefit in dealing with them. As well as working to oblige the Central Bank of Iraq to use the system in office and field oversight operations over banks operating in Iraq and to follow up on global developments related to systems specialized in financial and supervisory analysis for banks of all types.